2024
DOI: 10.1002/rmv.2532
|View full text |Cite
|
Sign up to set email alerts
|

Association between cytomegalovirus infection and neurological disorders: A systematic review

Samira Sanami,
Shahnam Shamsabadi,
Amir Dayhimi
et al.

Abstract: Cytomegalovirus (CMV) belongs to the Herpesviridae family and is also known as human herpesvirus type 5. It is a common virus that usually doesn't cause any symptoms in healthy individuals. However, once infected, the virus remains in the host's body for life and can reactivate when the host's immune system weakens. This virus has been linked to several neurological disorders, including Alzheimer's disease, Parkinson's disease, Autism spectrum disorder, Huntington's disease (HD), ataxia, Bell's palsy (BP), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 216 publications
(462 reference statements)
0
0
0
Order By: Relevance
“…Two more recent studies have also attempted to address these discrepancies in the research literature. A comprehensive review by Sanami et al [61] suggested that while HCMV appears to promote immune and inflammatory processes that are associated with biomarkers of Alzheimer's disease, HCMV is more likely a risk factor for Alzheimer's disease and not a causal factor per se. Furthermore, Ji et al [62] used meta-analytic methods to examine the potential association between HCMV and Alzheimer's disease.…”
Section: Hcmv and Dementiamentioning
confidence: 99%
“…Two more recent studies have also attempted to address these discrepancies in the research literature. A comprehensive review by Sanami et al [61] suggested that while HCMV appears to promote immune and inflammatory processes that are associated with biomarkers of Alzheimer's disease, HCMV is more likely a risk factor for Alzheimer's disease and not a causal factor per se. Furthermore, Ji et al [62] used meta-analytic methods to examine the potential association between HCMV and Alzheimer's disease.…”
Section: Hcmv and Dementiamentioning
confidence: 99%